Ana Batik Magelang’s Business Development Strategy Based on SWOT and Business Model Canvas - Tri Puji Hastutik; Ivo Novitaningtyas (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze Ana Batik's business conditions as one of the MSMEs in Magelang based on the Business Model Canvas (BMC) analysis to develop a business strategy based on a SWOT analysis. The research was developed based on a descriptive qualitative approach. The data used in this study are primary data and secondary data. Primary data were collected through observation and interviews, while secondary data were collected through literature studies. The data that has been collected is analyzed based on the Business Model Canvas (BMC) analysis and the SWOT analysis. The Business Model Canvas (BMC) analysis is used to describe Ana Batik's business conditions, while the SWOT analysis is used to formulate a business development strategy that is applied to the new business model. The results of the data analysis indicate that the appropriate strategy for Ana Batik Magelang's business development is the SO strategy. SO strategies that can be applied are developing products according to fashion trends, using brand ambassadors to attract and increase consumer buying interest, and expand the market to the scope of the global market. By implementing this strategy, it is hoped that Ana Batik Magelang's business can develop and be sustainable.